Using simplified models to simulate dynamics in process operations - Bonem, Joe M. (Knovel, 2012)
"The dynamics of process operations are often overlooked in the undergraduate chemical engineering curriculum. In addition, they are often overlooked or inadequately considered in process design and preparation of operating procedures for new facilities."--Knovel.
Knovel brief article.
At head of title: Cases.
Keywords: Industrial engineering -- Simulation methods.; Chemical engineering.; elektronické knihy; electronic books